2021
DOI: 10.3390/biology10050364
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Molecular Hydrogen Water Is Beneficial to Cardiovascular Function in Diet-Induced Obesity Mice

Abstract: Molecular hydrogen (MH) reportedly exerts therapeutic effects against inflammatory diseases as a suppressor of free radical chain reactions. Here, the cardiovascular protective effects of the intake of molecular hydrogen water (MHW) were investigated using high-fat diet-induced obesity (DIO) mice. MHW was prepared using supplier sticks and degassed water as control. MHW intake for 2 weeks did not improve blood sugar or body weight but decreased heart weight in DIO mice. Moreover, MHW intake improved cardiac hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Research by Masuda et al showed that a short H 2 intervention (2 weeks) had no effect on the blood sugar level in HFD-induced-obesity mice but changed the anti-metabolic phenotype of both WAT and BAT adipocytes, from hypertrophic to hyperplastic [73]. The findings of H 2 -induced rapid regulation of lipid metabolism in this study, along with evidence from other studies, such as the reduction in hepatic fat accumulation and the promotion of fatty acid metabolic gene expression in the liver found in obese mice after 1-2 weeks of HRW intake [17,71], indicated that H 2 could restore lipid metabolism toward energy consumption more favorably than glucose metabolism. In addition to the suppression of oxidative stress and inflammation, the regulation of gut microbiota [72], the alleviation of oxidized phospholipid (OxPLs) accumulation by enhancing the anti-oxidative capacity of HDL [74], as well as the acceleration of BAT activation [73] may be involved in the anti-obesity effects of H 2 .…”
Section: Obesitysupporting
confidence: 75%
See 1 more Smart Citation
“…Research by Masuda et al showed that a short H 2 intervention (2 weeks) had no effect on the blood sugar level in HFD-induced-obesity mice but changed the anti-metabolic phenotype of both WAT and BAT adipocytes, from hypertrophic to hyperplastic [73]. The findings of H 2 -induced rapid regulation of lipid metabolism in this study, along with evidence from other studies, such as the reduction in hepatic fat accumulation and the promotion of fatty acid metabolic gene expression in the liver found in obese mice after 1-2 weeks of HRW intake [17,71], indicated that H 2 could restore lipid metabolism toward energy consumption more favorably than glucose metabolism. In addition to the suppression of oxidative stress and inflammation, the regulation of gut microbiota [72], the alleviation of oxidized phospholipid (OxPLs) accumulation by enhancing the anti-oxidative capacity of HDL [74], as well as the acceleration of BAT activation [73] may be involved in the anti-obesity effects of H 2 .…”
Section: Obesitysupporting
confidence: 75%
“…In addition, previous studies also provided further evidence to explain how H 2 exerts protective effects against metabolic diseases through antioxidation. Ohta's group performed a microarray analysis to examine the changes in hepatic gene expression at different time points of H 2 treatment in obesity mice [71]. Combined with their previous findings, they speculated that H 2 reduced hydroxyl radicals, resulting in a decrease of peroxides and their end products, including 4-HNE, and thus activating PGC-1α through suppression of Akt/FoxO1 phosphorylation, followed by stimulation of the PPARα pathway, upregulation of FGF21 gene expression, and finally enhancing the fatty acid metabolism.…”
Section: Anti-oxidative Effects Of Hmentioning
confidence: 99%
“…PGC-1α protein accumulation has also shown increases in uncoupled respiration in BAT. Previously, HRW was linked to an increase in UCP1 expression in the BAT of high-fat diet-induced obesity mice [ 10 ]. UCP1 is an important thermogenic factor in BAT mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, H 2 could stimulate the gene expression of the transcriptional coactivator, peroxisome proliferator-activated receptor 1alpha (PGC-1α), to enhance fatty acid metabolism [ 9 ]. HRW is also associated with increased uncoupling protein 1 (UCP1) expression in brown adipose tissue (BAT) [ 10 ]. A high concentration of HRW could activate BAT thermogenesis and/or browning of white adipose tissue, potentially leading to increased energy expenditure phenotypes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting preclinical trial by a Japanese group [6] reported that drinking HRW for 2 weeks promoted the histological conversion of hypertrophy to hyperplasia in brown adipose tissues (BAT) with the upregulation of uncoupling protein 1 (UCP1, thermogenin), a critical thermogenic factor in BAT mitochondria. Specifically, HRW was associated with a 1.63-fold increase in UCP1 expression in the BAT of high-fat diet-induced obesity mice.…”
mentioning
confidence: 99%